ответ:
пошаговое объяснение:
1
1) (-∞; 0)∪(0; +∞)
2) (-∞; 3)∪(3; +∞)
3) (-∞; 7)∪(7; +∞)
4) (-∞; 0)∪(0; +∞)
5) (-∞; 1)∪(1; +∞)
6) (-∞; -4)∪(-4; 4)∪(4; +∞)
7) (-∞; -11)∪(-11; 2)∪(2; +∞)
2
1)=2/3
2)=b/c
3)=b/c
4)=b/y
5)=((a(a-b))/ac=(a-b)/c
6)=((a(a-b))/((a(a+b))=(a-b)/(a+c)
7)аналогично
8)аналогично
9)аналогично
10)=((x-1)(x+1))/((x(x-1))=(x+1)/x
11)=x^2/((x(x+1))=x/(x+1)
12)также как и 10
13)=1/m
14)=(a-3b)/((a-3b)(a+3b)=1/(a+3b)
15)=p
16)=так же как и 14
17)=((a-b)^2)/(a-b)=a-b
18)далее аналогично
10 11/24 и 8 19/36 нужно найти общий знаменатель
10 11/24×3= 10 33/72 и 8 19/36 × 2= 8 38/72
10 33/72-8 38/72= 9 105/72-8 38/72= 1 67/72
ответ: 1 целая 67/72